Retrospective Analysis of Episiotomy Rate in Erciyes University - Mehmet Serdar KÜTÜK; Mehmet Dolanbay; Mahmut Tuncay Özgün; Fatma Özdemir; Ahmet Öztürk; Ercan Aygen (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The purpose of the study was to assess the episiotomy rate and perineal outcome in women delivered in 2013-2014. STUDY DESIGN: Birth data and perineal outcome of women delivering singleton, live- born infant weighting more than 1000 gram in 2013- 2014 in Erciyes University Department of Obstetrics and Gynecology were evaluated retrospectively. RESULTS: A total of 580 birth occurred in our clinics in 2013- 2014. The mean maternal age 27.6±6.2 (min- max: 16-46 years), parity 1.17±1.2 (min- max: 0-14), birth weight 3033.1± 610 (min- max: 1070-4580 gram). The episiotomy rate for whole population was 19.4%. The episiotomy rate for multiparous and nulliparous were 6.1%, and 43.1% respectively. No cases of third and/or fourth degree perineal trauma were detected during the study period. The most common episiotomy indication was unfavorable pelvic examination (n: 35, 31.2%). CONCLUSION: Restrictive episiotomy application does not increase third and fourth degree perineal lacerations. With the increasing experiences and training, the episiotomy ratio can be further decreased in nulliparous women.